Studies on coordination chemistry and bioactivity of complexes of Ni(II) and Cu(II) containing some nitrogen-sulphur donor ligands - Nagalingam, Saravanan (2001)
Several Schiff bases of S-benzyldithiocarbazate (SBDTC) and Smethyldithiocarbazate (SMDTC) have been synthesised. Complexes of NiCll) and Cu(IT) were prepared. These compounds were characterised by elemental analyses and various physico-chemical techniques. The Schiff bases and their metal complexes were tested to evaluate their cytotoxic, antimicrobial and antioxidant activities. Cytotoxic screening was carried out against the T-Iymphoblastic leukemic cells (CEM-SS) and colon cancer cells (HT-29). Antimicrobial screening was carried out against four bacteria and four fungi. The nickelCTI) complexes are four- and five- coordinated while the copper(TI) complex is five-coordinated.